2000
DOI: 10.1046/j.1365-2265.2000.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor I administration induces fluid and sodium retention in healthy adults: possible involvement of renin and atrial natriuretic factor

Abstract: IGF-I treatment causes fluid and sodium retention. This may be mediated by increased renin release and suppression of atrial natriuretic factor. The present data suggest that the fluid and sodium retaining effect of GH is at least partly mediated through IGF-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 38 publications
2
38
0
1
Order By: Relevance
“…It has been suggested that several effects of GH are at least partly mediated by insulin-like growth factor I (IGF-I) (591). Indeed, it has been found that IGF-I increases PRA in rats and fetal sheep and stimulates the secretion of renin from renal cortical slices (392,408,563,564), but the precise role of IGF-I for GH-induced renin release is unknown.…”
Section: Growth Hormone and Insulin-like Growth Factor Imentioning
confidence: 99%
“…It has been suggested that several effects of GH are at least partly mediated by insulin-like growth factor I (IGF-I) (591). Indeed, it has been found that IGF-I increases PRA in rats and fetal sheep and stimulates the secretion of renin from renal cortical slices (392,408,563,564), but the precise role of IGF-I for GH-induced renin release is unknown.…”
Section: Growth Hormone and Insulin-like Growth Factor Imentioning
confidence: 99%
“…IGF-1 production is under strict control of growth hormone (GH). GH infusion to healthy humans increases renal IGF-1 production and stimulates renal Na + and fluid transport [125,133,222] which has been used to explain that patients with acromegaly (GH over-production) frequently develop arterial hypertension [36]. Recently, Kamenicky and coworkers studied acromegalic GC rats to analyse the molecular mechanism responsible for renal Na + retention in these rats.…”
Section: Regulation Of Enac By Insulin/igf-1mentioning
confidence: 99%
“…In addition to the direct effects of GH and IGF-1 on the vasculature, several other pathophysiological mechanisms have been postulated to contribute to hypertension in acromegaly [18], including GH-mediated increased renal tubular sodium reabsorption [19] and inhibition of atrial natriuretic peptide by IGF-1 [20]. Where present, elevated insulin levels may also lead to increased sodium reabsorption with activation of the renin-angiotensin-aldosterone system.…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%